Aggregate effects of vascular risk factors on cerebrovascular changes in autopsy‐confirmed Alzheimer's disease. Issue 4 (8th July 2014) - Bangen, Katherine J.; Nation, Daniel A.; Delano‐Wood, Lisa; Weissberger, Gali H.; Hansen, Lawrence A.; Galasko, Douglas R.; Salmon, David P.; Bondi, Mark W.
Abstract: We examined the relationships of antemortem vascular risk factors to postmortem cerebrovascular and Alzheimer's disease (AD) pathologies. Eighty‐four AD patients underwent an assessment of vascular risk (blood pressure, cholesterol, smoking, cardiovascular disease, diabetes, atrial fibrillation, transient ischemic attack [TIA], or stroke) and later underwent brain autopsy. Given our aim to examine mild cerebrovascular changes (CVCs), individuals were excluded if autopsy revealed large stroke. The most common forms of CVC were circle of Willis atherosclerosis followed by arteriosclerosis, lacunes, and microinfarcts. Excluding the history of TIA/clinical stroke, individual vascular risk factors were not associated with CVC. However, the presence of multiple vascular risk factors was associated with CVC. Furthermore, the presence of CVC was associated with lower Braak and Braak stage. These findings highlight the importance of aggregate risk in the vascular contribution to dementia. Interventions designed to maintain cerebrovascular health may represent important opportunities for preventing or delaying dementia, even when AD is the dominant pathology.